Report on the effectiveness of vegetative barriers to regulate simulated fluxes of runoff and sediment in open agricultural landscapes (Flanders, Belgium). (14th August 2021) - Frankl, Amaury; De Boever, Maarten; Bodyn, Jonas; Buysens, Saskia; Rosseel, Liesbet; Deprez, Sarah; Bielders, Charles; Dégre, Aurore; Stokes, Alexia
Abstract: Vegetative barriers are increasingly used to reduce sediment export from cropland and thus mitigate negative off‐site consequences of soil erosion. Here, we report and discuss the effectiveness of vegetative barriers implemented in Flanders (Belgium) to buffer the flows of water and sediment. The three types of vegetative barriers studied are made of straw bales, wood chips or bales of coconut‐ fibre. Based on three simulated runoff experiments performed in the field, we calculated the hydraulic roughness and sediment deposition ratio. Our experiments showed that the barriers made of coconut‐fibre bales performed markedly better than those of straw bales or wood chips (Manning's n values of 1.355, 1.049 and 2.231 s m ‐ 1/3 and a sediment deposition ratio of 19%, 38% and 64% for barriers made of straw bales, wood chips and coconut‐fibre bales, respectively, during the first experiment). These values increased during subsequent experiments demonstrating the effect of sediment accumulating inside the structures. Especially for coconut‐fibre bales, this accumulation increases the risk of runoff bypassing or overtopping the barriers. The barriers mainly retained sand and, to a lesser extent, silt and clay. As vegetative barriers have to be renewed every few years because of the decomposition of organic material, barriers made of locally available materials are more sustainable as a nature‐based solution to erosion. We conclude that although the vegetative barriers made of coconut‐fibre bales are superior in their regulation of flows of runoff and sediment, barriers made of locally sourced materials are more sustainable.